1H Nuclear Magnetic Resonance-Based Targeted and Untargeted Metabolomics Profiling of Retail Samples of Cuachalalate (Amphipterygium adstringens) - Erick Alejandro Herrera-Jurado; Estefanía De Jesús Terán-Sánchez; José Iván Serrano-Contreras; L. Gerardo Zepeda-Vallejo (Molecules)
Amphipterygium adstringens (cuachalalate) is a medicinal plant widely used in traditional Mexican medicine for its anti-inflammatory, gastroprotective, and antimicrobial properties. In this study, we applied qualitative and quantitative NMR-based metabolomics profiling, combined with multivariate statistical analyses, including Principal Component Analysis (PCA), Partial Least Squares Discriminant Analysis (PLS-DA), and S-plots, to evaluate the chemical composition and authenticity of A. adstringens samples collected from different commercial sources sold in Mexico City. Metabolomic profiles in organic and aqueous extracts revealed highly similar spectral patterns among all collected samples, supporting the consistency of commercially available A. adstringens in Mexico. The presence of 3α-hydroxy-masticadienoic acid (3α-HMDA) and anacardic acids, biomarkers of the genus, was confirmed by 1H NMR in hexane extracts; in the aqueous extract they were not observed with the same analytical platform. These findings suggest that the traditional infusion method may not effectively extract the above-mentioned key bioactive compounds. This approach enhances quality control and ensures the reliability of A. adstringens products in the commercial market.